Damping and silencing magnesium alloy and preparation method thereof

By designing a structural magnesium alloy with a sphere connected by air holes and preparing it using laser additive manufacturing technology, the problem of insufficient shock absorption of existing magnesium alloys is solved, high energy absorption and noise shielding are achieved, and shock absorption and sound silence of parts are improved. performance.

CN119410980APending Publication Date: 2025-02-11JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411524390.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The shock absorption of existing magnesium alloys in the aerospace and automotive fields still needs to be further improved to better improve the service performance of parts in complex environments.

Method used

A structural magnesium alloy with spherical pores connected is designed and developed, prepared by laser additive manufacturing technology, and the printing parameters are adjusted to achieve stable heterotropical performance and high energy absorption.

Benefits of technology

It achieves high energy absorption and noise shielding, improves the shock absorption and sound silence performance of magnesium alloy, is suitable for aerospace and automotive parts, and improves impact energy absorption and impact protection capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410980A_ABST
    Figure CN119410980A_ABST
Patent Text Reader

Abstract

The magnesium alloy comprises the following components in percentage by mass: 9.53% of aluminum, 0.59% of zinc, 0.28% of manganese, 0.0025% of iron, 0.04% of silicon, 0.003% of copper and the balance of magnesium element. The invention also discloses a preparation method of the shock-absorbing and noise-reducing magnesium alloy, which comprises the following steps: step 1, determining the components and weight of the magnesium alloy powder, preheating the powder of each component in a vacuum drying oven, and taking out the powder after cooling; secondly, a magnesium alloy base plate is selected and preheated; thirdly, modeling is conducted on the three-dimensional structure of the magnesium alloy, a model is stored and transmitted into layering software, and after slicing layering treatment is conducted, the model is guided into selective laser melting additive manufacturing equipment; fourthly, the selective laser melting additive manufacturing equipment is started, and printing parameters are set; and fifthly, the structural magnesium alloy formed part obtained through printing is cut and separated from the base plate, and a structural magnesium alloy finished product is obtained after polishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnesium alloy for vibration reduction and noise reduction and a preparation method thereof, belonging to the technical field of metal material preparation. Background Art

[0002] Magnesium alloys have broad application prospects in aerospace, new energy vehicles, and biomedicine due to their excellent properties such as light weight, high specific strength, shock absorption, thermal conductivity, and electrical conductivity. In the fields of aerospace and automobiles, the shock absorption of magnesium alloy materials still needs to be further improved in order to better improve the service performance of parts in complex environments. The structure of the structural magnesium alloy of the present invention connected by pores is conducive to the absorption of energy, making the formed parts impact-resistant, thereby achieving high-energy absorption. At the same time, the structural magnesium alloy has better energy absorption than structural aluminum alloys and plastics. Therefore, a very important application field of structural magnesium alloys is impact energy absorption and impact protection materials, such as installing a structural magnesium alloy bumper in front of the car to effectively absorb the energy of the frontal impact or using structural magnesium alloys in the manufacture of automobile buffers, bases, chassis, etc. Structural magnesium alloys can not only be used as energy-absorbing materials for low-speed impacts, but can also be used as attenuation and protection materials in the military for impact protection materials of armored vehicles, and also have the function of eliminating noise.

[0003] At present, laser additive manufacturing technology is to build a three-dimensional model and then use the method of layer-by-layer printing to realize the formation of complex and precise parts by using the high temperature effect of laser beam on metal powder. Compared with the high cost, long cycle and inability to cast complex structural parts of traditional casting process, laser additive manufacturing technology can quickly process parts with complex and precise structures, and ensure that the parts have high dimensional accuracy, no crack defects and stable performance. In the SLM (selective laser melting) process, the contour parameters of each section are obtained by slicing and layering the three-dimensional digital model of the part, and then the metal powder is evenly spread on the surface of the substrate according to the thickness of the slice layer. The high-energy laser beam selectively melts and quickly solidifies the metal powder according to the contour parameters. After each layer of laser melting, the next layer of powder is spread, and the three-dimensional solid parts are manufactured by melting, solidifying and accumulating layer by layer. In the SLM processing process, the interaction between the high-energy laser beam and the loose powder layer involves many complex physical and chemical phenomena, including light energy absorption, heat transfer and mass transfer, and chemical reactions. These reactions can improve the interface bonding between the reinforcing particles and the matrix, and finally the material printed by SLM technology has the characteristics of fine and uniform structure. Summary of the invention

[0004] The present invention designs and develops a magnesium alloy for vibration reduction and noise reduction, which is a structure in which spheres are connected by pores. The molded parts are impact-resistant and can absorb high energy. The whole has high strength and good ductility, can shield noise, and achieve vibration reduction and noise reduction.

[0005] The present invention also designs and develops a method for preparing a shock-absorbing and noise-absorbing magnesium alloy based on a laser additive manufacturing method, and adjusts the printing and manufacturing parameters during the processing. Through parameter adjustment, the anisotropic properties are stabilized without crack defects, the dimensional accuracy of the molded parts is improved, and the processing cost and cycle are reduced.

[0006] The technical solution provided by the present invention is:

[0007] A magnesium alloy for vibration reduction and noise reduction and a preparation method thereof, wherein the magnesium alloy comprises the following components in terms of mass percentage:

[0008] Aluminum 9.53%, zinc 0.59%, manganese 0.28%, iron 0.0025%, silicon 0.04%, copper 0.003%, and the balance is magnesium.

[0009] Preferably, the vibration-absorbing and noise-absorbing magnesium alloy is a structural magnesium alloy, which comprises:

[0010] There are multiple bubble capsules, each of which has multiple air holes on its wall, and adjacent bubble capsules are connected through the air holes; wherein the bubble capsule is a spherical structure, and air holes are formed in six directions on the sphere for absorbing and filtering energy.

[0011] A method for preparing a magnesium alloy for vibration reduction and noise reduction, comprising:

[0012] Step 1, determining the composition and weight of the magnesium alloy powder, and preheating the powders of each component in a vacuum drying oven;

[0013] Step 2: Select a magnesium alloy substrate and preheat the substrate;

[0014] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0015] Step 4: Start the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power range is 60-150W, scanning rate range is 400-600mm / s, laser filling spacing range is 40-50μm, print the structural magnesium alloy, cool it after printing, and take it out after cooling to below 50°C;

[0016] Step 5: Cut and separate the printed structural magnesium alloy molded part from the substrate, and obtain a structural magnesium alloy finished product after polishing.

[0017] Preferably, in step 4, the structural magnesium alloy is printed in layers, and the angle between adjacent powder layers in the laser scanning direction is 67°.

[0018] Preferably, in step 4, the spot size is set to 45±4 μm and the stripe width is set to 5 mm.

[0019] Preferably, the particle size of the magnesium alloy powder is 15 to 53 μm.

[0020] Preferably, in step 4, the printing parameters are set as follows: laser power is 120 W, scanning rate is 500 mm / s, and laser filling spacing is 45 μm.

[0021] The beneficial effects of the present invention are:

[0022] The structural magnesium alloy provided by the present invention, wherein the structure in which the spheres are connected by pores is conducive to the absorption and filtration of energy. When the energy passes through, it undergoes repeated conversion between the spheres and the pores, and both the flow rate and the flow velocity will undergo a progressive attenuation change, and the energy in each impact direction can be absorbed. Compared with the closed-cell type, the round-walled pores have a longer buffering time when receiving impact energy and do not rebound, do not accumulate energy, and suddenly release it to cause greater damage, which is suitable for improving the safety performance of aerospace and automobile collisions. In terms of structural lightweighting, the magnesium alloy has a low density and high specific strength, which meets the strength requirements of aerospace and automobile parts, and can reduce weight at the same time. In terms of functional materials, structural magnesium alloys have the characteristics of energy consumption and are used to reduce noise.

[0023] The preparation method of the invention can produce parts with high dimensional accuracy, no crack defects, uniform pore size, and stable anisotropic performance. The invention can provide new ideas and solutions for preparing structural magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the three-dimensional structure of the vibration-absorbing and noise-absorbing magnesium alloy of the present invention.

[0025] Figure 2 This is a front view of the vibration-absorbing and noise-absorbing magnesium alloy of the present invention.

[0026] Figure 3 It is a side view of the magnesium alloy for vibration reduction and noise reduction according to the present invention.

[0027] Figure 4 This is a top view of the vibration-absorbing and noise-absorbing magnesium alloy of the present invention.

[0028] Figure 5 This is a front view SEM image of the microstructure of the vibration-absorbing and noise-absorbing magnesium alloy prepared in Example 1 of the present invention.

[0029] Figure 6 This is a side view SEM image of the microstructure of the vibration-absorbing and noise-absorbing magnesium alloy prepared in Example 1 of the present invention.

[0030] Figure 7This is a top view SEM image of the microstructure of the vibration-absorbing and noise-absorbing magnesium alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0032] like Figure 1-7 As shown, the present invention provides a magnesium alloy for vibration reduction and noise reduction, which is a structure in which spheres are connected by pores. The formed parts are impact-resistant and can absorb high energy. The whole has high strength and good ductility, and can achieve vibration reduction and noise reduction.

[0033] A magnesium alloy for vibration reduction and noise reduction, comprising the following components by mass percentage:

[0034] Aluminum 9.53%, zinc 0.59%, manganese 0.28%, iron 0.0025%, silicon 0.04%, copper 0.003%, and the balance is magnesium.

[0035] In the present invention, as a preferred embodiment, the vibration-absorbing and noise-absorbing magnesium alloy is a structural magnesium alloy, which includes:

[0036] There are multiple bubble capsules, each of which has multiple air holes on its wall, and adjacent bubble capsules are connected via the air holes; wherein the bubble capsule is a spherical structure, and air holes are formed in six directions on the sphere.

[0037] It is equivalent to a dense magnesium alloy hollowed out by multiple tightly stacked hollow balls. The bubble cabin is spherical and relatively regular. The spheres are arranged very closely. Small circular holes are opened on each cabin wall to connect to other spheres, forming air holes in six directions for absorbing and filtering energy.

[0038] The present invention also provides a method for preparing a vibration-absorbing and noise-absorbing magnesium alloy, comprising:

[0039] Step 1, determine the composition and weight of the magnesium alloy powder, and preheat the powder of each component in a vacuum drying oven, and take it out after cooling;

[0040] Weighed by mass percentage, aluminum 9.53%, zinc 0.59%, manganese 0.28%, iron 0.0025%, silicon 0.04%, copper 0.003%, and the balance is magnesium;

[0041] The powders of each component were preheated in a vacuum drying oven at 120°C for 2 hours;

[0042] Step 2: Select a magnesium alloy substrate with the same composition and preheat the substrate. The preheating temperature of the substrate is ≥ 160°C;

[0043] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0044] Among them, the structural magnesium alloy is saved as an output format file in STL format and transferred to the layering software;

[0045] Step 4: Start the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power range is 60-150W, scanning rate range is 400-600mm / s, laser filling spacing range is 40-50μm, print the structural magnesium alloy, and cool it to 50°C after printing and take it out;

[0046] The included angle of the laser scanning direction between two adjacent paving layers was set to 57°, the spot size was set to 45±4 μm, and the stripe width was set to 5 mm.

[0047] Step 5: cutting and separating the printed structural magnesium alloy molded part from the substrate, and polishing to obtain a structural magnesium alloy finished product, including:

[0048] Performing wire cutting along the end surface of the substrate to cut and separate the structural magnesium alloy formed part from the substrate to obtain the structural magnesium alloy;

[0049] In the present invention, as a preferred embodiment, the particle size of the magnesium alloy powder is in the range of 15 to 53 μm.

[0050] Example 1

[0051] Step 1: Determine the composition of the magnesium alloy powder as follows: 9.53% aluminum, 0.59% zinc, 0.28% manganese, 0.0025% iron, 0.04% silicon, 0.003% copper, and the balance is magnesium;

[0052] The powders of each component were preheated in a vacuum drying oven at 120°C for 2 hours;

[0053] Step 2: Select a magnesium alloy substrate with the same composition and preheat the substrate. The preheating temperature of the substrate is ≥ 160°C;

[0054] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0055] Among them, the structural magnesium alloy is saved as an output format file in STL format and transferred to the layering software;

[0056] Step 4: Turn on the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power of 120W, scanning rate of 500mm / s, laser filling spacing of 45μm, print the structural magnesium alloy, and cool it to 50℃ after printing.

[0057] Step 5: Performing wire cutting along the end surface of the substrate to separate the structural magnesium alloy molded part from the substrate to obtain a structural magnesium alloy; performing electrochemical polishing on the obtained structural magnesium alloy;

[0058] In the present invention, as a preferred embodiment, a perchloric acid alcohol solution is used as a polishing and corrosive solution to perform electrochemical polishing treatment on the structural magnesium alloy.

[0059] The relative density was measured using an analytical balance according to the Archimedean principle. The results are shown in Table 1.

[0060] The microhardness of the sample was measured using a Vickers hardness tester with a load of 100 gf and an indentation time of 20 s. Ten random indentations were performed on the polished surface, and the average microhardness value was calculated.

[0061] Example 2

[0062] Step 1: Determine the composition of the magnesium alloy powder as follows: 9.53% aluminum, 0.59% zinc, 0.28% manganese, 0.0025% iron, 0.04% silicon, 0.003% copper, and the balance is magnesium;

[0063] The powders of each component were preheated in a vacuum drying oven at 120°C for 2 hours;

[0064] Step 2: Select a magnesium alloy substrate with the same composition and preheat the substrate. The preheating temperature of the substrate is ≥ 160°C;

[0065] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0066] Among them, the structural magnesium alloy is saved as an output format file in STL format and transferred to the layering software;

[0067] Step 4: Turn on the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power of 60W, scanning rate of 400mm / s, laser filling spacing of 40μm, print the structural magnesium alloy, and cool it to 50℃ after printing.

[0068] Step 5: Performing wire cutting along the end surface of the substrate to separate the structural magnesium alloy molded part from the substrate to obtain a structural magnesium alloy; performing electrochemical polishing on the obtained structural magnesium alloy;

[0069] In the present invention, as a preferred embodiment, a perchloric acid alcohol solution is used as a polishing and corrosive solution to perform electrochemical polishing treatment on the structural magnesium alloy.

[0070] The relative density was measured using an analytical balance according to the Archimedean principle. The results are shown in Table 1.

[0071] The microhardness of the sample was measured using a Vickers hardness tester with a load of 100 gf and an indentation time of 20 s. Ten random indentations were performed on the polished surface, and the average microhardness value was calculated.

[0072] Example 3

[0073] Step 1: Determine the composition of the magnesium alloy powder as follows: 9.53% aluminum, 0.59% zinc, 0.28% manganese, 0.0025% iron, 0.04% silicon, 0.003% copper, and the balance is magnesium;

[0074] The powders of each component were preheated in a vacuum drying oven at 120°C for 2 hours;

[0075] Step 2: Select a magnesium alloy substrate with the same composition and preheat the substrate. The preheating temperature of the substrate is ≥ 160°C;

[0076] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0077] Among them, the structural magnesium alloy is saved as an output format file in STL format and transferred to the layering software;

[0078] Step 4: Turn on the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power of 150W, scanning rate of 600mm / s, laser filling spacing of 50μm, print the structural magnesium alloy, and cool it to 50℃ after printing.

[0079] Step 5: Performing wire cutting along the end surface of the substrate to separate the structural magnesium alloy molded part from the substrate to obtain a structural magnesium alloy; performing electrochemical polishing on the obtained structural magnesium alloy;

[0080] In the present invention, as a preferred embodiment, a perchloric acid alcohol solution is used as a polishing and corrosive solution to perform electrochemical polishing treatment on the structural magnesium alloy.

[0081] The relative density was measured using an analytical balance according to the Archimedean principle. The results are shown in Table 1.

[0082] The microhardness of the sample was measured using a Vickers hardness tester with a load of 100 gf and an indentation time of 20 s. Ten random indentations were performed on the polished surface, and the average microhardness value was calculated.

[0083] Example 4

[0084] Step 1: Determine the composition of the magnesium alloy powder as follows: 9.53% aluminum, 0.59% zinc, 0.28% manganese, 0.0025% iron, 0.04% silicon, 0.003% copper, and the balance is magnesium;

[0085] The powders of each component were preheated in a vacuum drying oven at 120°C for 2 hours;

[0086] Step 2: Select a magnesium alloy substrate with the same composition and preheat the substrate. The preheating temperature of the substrate is ≥ 160°C;

[0087] Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering;

[0088] Among them, the structural magnesium alloy is saved as an output format file in STL format and transferred to the layering software;

[0089] Step 4: Turn on the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power of 105W, scanning rate of 500mm / s, laser filling spacing of 45μm, print the structural magnesium alloy, and cool it to 50℃ after printing.

[0090] Step 5: Performing wire cutting along the end surface of the substrate to separate the structural magnesium alloy molded part from the substrate to obtain a structural magnesium alloy; performing electrochemical polishing on the obtained structural magnesium alloy;

[0091] In the present invention, as a preferred embodiment, a perchloric acid alcohol solution is used as a polishing and corrosive solution to perform electrochemical polishing treatment on the structural magnesium alloy.

[0092] The relative density was measured using an analytical balance according to the Archimedean principle. The results are shown in Table 1.

[0093] The microhardness of the sample was measured using a Vickers hardness tester with a load of 100 gf and an indentation time of 20 s. Ten random indentations were performed on the polished surface, and the average microhardness value was calculated.

[0094] Table 1

[0095]

[0096] It can be seen from Table 1 that in order to obtain an SLM parameter combination with high density and microhardness, the present invention uses a response optimizer to further determine appropriate processing parameters and their predicted values, and finally determines the printing parameters of Example 1 (P = 120W, v = 500mm / s, h = 45μm) as the optimal combination. The obtained structural magnesium alloy has a relative density of 99.5±0.28%, a microhardness of 95.6±5.28HV, an elastic modulus of 39.8-42.4GPa, a strength UTS = 370.2MPa, and a ductility At = 10.4%.

[0097] like Figure 5-7 As shown in the figure, it can be seen that the SLM printed samples of the vibration-absorbing and noise-absorbing magnesium alloy structural parts prepared in Example 1 in three directions (front, side, and top) are mainly equiaxed crystals and cellular crystals. The microstructure of fine grain size has more grain boundaries. The more grain boundaries there are, the more obvious the dislocation blocking effect is, resulting in dislocation accumulation, thereby improving the material strength. The absence of slender columnar crystals indicates that the temperature gradient is small and the temperature environment is close to being insufficient to form columnar crystals, and the degree of supercooling is small. Among them, the grain size, grain aspect ratio, and their crystallographic orientation relative to the outer surface of the component are controlled by the local solidification conditions where the directional heat flux and the relevant thermal gradient exist.

[0098] The reason why SLM produces fine equiaxed crystals and cellular crystals is that the laser beam scans the powder layer to form a high-temperature molten pool. Under the action of temperature difference and surface tension, the liquid metal undergoes martensitic effect and forms a cellular liquid phase region. After rapid cooling and solidification, equiaxed crystals and cellular crystals are formed, each of which can withstand loads and disperse stress, thereby increasing the strength and stiffness of the material. Local time-temperature changes dominate many phenomena: (1) the completeness of liquid phase homogenization; (2) the distribution of elements between the liquid and solid phases and the (super) saturation of the solid phase; (3) the supercooling that promotes nucleation and grain growth conditions; (4) shrinkage and pore formation after solidification; (5) homogenization and solid solution decomposition (aging); (6) the formation of residual stress and its spatial distribution. In addition, the rapid cooling rate of SLM (103℃ / s~106℃ / s) promotes the formation of non-equilibrium supersaturated solid solution, which is beneficial to improve material properties.

[0099] In response to the technical difficulties of structural magnesium alloys in terms of difficulty in preparation, low strength and ductility, and insufficient shock absorption, the present invention uses selective laser melting (SLM) additive manufacturing technology to obtain a shock-absorbing and sound-absorbing magnesium alloy formed part, which has a high relative density, uniform grain size, and no crack defects. It has high strength and good ductility as a whole. The structure of the spheres connected by pores is conducive to energy absorption, making the formed part impact-resistant, thereby achieving high energy absorption and noise shielding.

[0100] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A magnesium alloy for vibration and noise reduction, characterized in that: The magnesium alloy comprises the following components in terms of mass percentage: Aluminum 9.53%, zinc 0.59%, manganese 0.28%, iron 0.0025%, silicon 0.04%, copper 0.003%, and the balance is magnesium.

2. The magnesium alloy for vibration and noise reduction according to claim 1, characterized in that: The vibration-absorbing and noise-absorbing magnesium alloy is a structural magnesium alloy, which includes: There are multiple bubble capsules, each of which has multiple air holes on its wall, and adjacent bubble capsules are connected through the air holes; wherein the bubble capsule is a spherical structure, and air holes are formed in six directions on the sphere for absorbing and filtering energy.

3. A method for preparing a magnesium alloy for vibration and noise reduction, characterized in that: include: Step 1, determining the composition and weight of the magnesium alloy powder, and preheating the powders of each component in a vacuum drying oven; Step 2: Select a magnesium alloy substrate and preheat the substrate; Step 3: Model the three-dimensional structure of the magnesium alloy, save and transfer the model to the layering software, and then import it into the laser selective melting additive manufacturing equipment after slicing and layering; Step 4: Start the laser selective melting additive manufacturing equipment, set the printing parameters as follows: laser power range is 60-150W, scanning rate range is 400-600mm / s, laser filling spacing range is 40-50μm, print the structural magnesium alloy, cool it after printing, and take it out after cooling to below 50°C; Step 5: Cut and separate the printed structural magnesium alloy molded part from the substrate, and obtain a structural magnesium alloy finished product after polishing.

4. The method for preparing the vibration-absorbing and noise-absorbing magnesium alloy according to claim 3, characterized in that: In the step 4, the structural magnesium alloy is printed in layers, and the angle between adjacent powder layers in the laser scanning direction is 67°.

5. The method for preparing the vibration-absorbing and noise-absorbing magnesium alloy according to claim 4, characterized in that: In step 4, the spot size is set to 45±4 μm and the stripe width is set to 5 mm.

6. The method for preparing the vibration-absorbing and noise-absorbing magnesium alloy according to claim 5, characterized in that: The particle size of the magnesium alloy powder is 15 to 53 μm.

7. The method for preparing the vibration-absorbing and noise-absorbing magnesium alloy according to claim 3 or 6, characterized in that: In step 4, the printing parameters are set as follows: laser power is 120 W, scanning rate is 500 mm / s, and laser filling spacing is 45 μm.